Margaret McMillan’s Contributions to Cultures of Childhood - Betty Liebovich (Genealogy)
Margaret McMillan is widely known for her open-air nursery, making it her life mission to live by the McMillan family motto, Miseris Succurrere Disco, which translates to ‘I endeavour to care for the less fortunate’. Margaret and her sister, Rachel, dedicated their lives to improving living conditions for the poor and working class in England and created health and dental clinics for them in Bradford, Bow and Deptford. During the 1889 Dock Strike, Margaret and Rachel supported workers by marching and demonstrating at Parliament. At the turn of the last century, they were instrumental in inspiring legislation for children’s welfare and education on both local and national levels in England. Their efforts led to campaigning for the 1906 Provision of School Meals Act and medical inspections for primary school children. In an effort to improve health conditions for the children living in the Deptford community, they created night camps for deprived children in 1908. With war impending in 1914, they created the first open air nursery in England in order to serve the disadvantaged community surrounding it, providing a safe and nurturing learning environment for the young children of the women going to work in place of the men who were called up to war. Margaret McMillan’s ideals for young children’s nurture and education continue to influence how we educate children in contemporary England and are woven into the fabric of our goals for young children’s futures.